1979
DOI: 10.1007/bf00890691
|View full text |Cite
|
Sign up to set email alerts
|

Psychological dimensions of social networks: A multimethod analysis

Abstract: Two exploratory studies are reported which sought to iden@ important psychological dimensions of social networks. Both studies investigated the social networks of college students, using as subfects the same 16 male and 16 female students. The first study employed multiple regression to generate predictor variables to students'ratings of satisfaction with their social network. The second study assessed how structurally contrasting social networks might function as natural support systems during a period of env… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
121
2
5

Year Published

1983
1983
2015
2015

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(134 citation statements)
references
References 13 publications
6
121
2
5
Order By: Relevance
“…En esta nueva situación social comienza a tomar vital protagonismo el consumo, sobre todo en niños y adolescentes a modo de compensación por la ausencia constante de sus progenitores. Paradójicamente, el 2 Como ejemplo de ello puede tomarse la investigación sobre la influencia persuasiva de los estímulos eróticos en las publicidades, que realizada por Hugo Mastrodoménico (2012) (Hirsch, 1979). Las redes personales inciden en la calidad de vida ya que sirven como fuente de apoyo de recursos emocionales (intercambio afectivo, sostén, expresión de emociones y sentimientos, manifestaciones afectivas), informacionales (intercambio de diagnósticos contextuales, consejos, rumores), materiales (intercambio de recursos, bienes, dinero) y hasta axiológicos (legitimación de prácticas plausibles) de los individuos.…”
Section: Marco Teórico De Referenciaunclassified
“…En esta nueva situación social comienza a tomar vital protagonismo el consumo, sobre todo en niños y adolescentes a modo de compensación por la ausencia constante de sus progenitores. Paradójicamente, el 2 Como ejemplo de ello puede tomarse la investigación sobre la influencia persuasiva de los estímulos eróticos en las publicidades, que realizada por Hugo Mastrodoménico (2012) (Hirsch, 1979). Las redes personales inciden en la calidad de vida ya que sirven como fuente de apoyo de recursos emocionales (intercambio afectivo, sostén, expresión de emociones y sentimientos, manifestaciones afectivas), informacionales (intercambio de diagnósticos contextuales, consejos, rumores), materiales (intercambio de recursos, bienes, dinero) y hasta axiológicos (legitimación de prácticas plausibles) de los individuos.…”
Section: Marco Teórico De Referenciaunclassified
“…This idea is congruent with the literature on adult development emphasizing the centrality of relationships and the importance of attachment for a woman's sense of self (Gilligan, 1982;Miller, 1976). Research also indicates women reportedly have more supportive relationships in their networks than men (Hirsch, 1979;Leavy, 1983). Yet, in this study both men and women reported that their social networks were important to them in their daily lives.…”
Section: Personal Strategiesmentioning
confidence: 99%
“…Al though the evidence is inconclusive (LaRocco and Jones, 1978;Pinneau, 1975;Thoits, 1982), several studies lend credence to this argument (Gore, 1978;Hirsch, 1979;Lowenthal and Haven, 1968;Nuckolls et al, 1972). There is also evidence that social support has direct or main effects on psychological symptomatology (Andrews, Tennant, Hewson, and Vaillant, 1978;Lin, Ensel, Simeone, and Kuo, 1979;Turner, 1981).…”
Section: Social Network and Social Support: Stress And Well-beingmentioning
confidence: 99%
“…Most social network research centers around positive influences, that is, influences of network patterns upon such things as improved functioning, health protective behaviors, and resource utilization (Cleary, 1987;Hirsch, 1979;Mitchell & Trickett, 1980). The concept however can also be useful to examine dysfunctional impacts such as influences toward mixing alcohol with risky sexual behavior.…”
Section: Social Network Theorymentioning
confidence: 99%
“…The concept can also be useful to examine dysfunctional impacts such as influences toward involving alcohol with risky sexual behavior. Hirsch (1979) Holohoan and Wilcox, (1978) found that friendship formation patterns in university residences differed as a function of both dormitory type, which dictated the structure of the network, and social competence of the member.…”
Section: Social Networkmentioning
confidence: 99%